Dynastic Measures of Intergenerational Mobility - Olivier Bargain; Maria C. Lo Bue; Flaviana Palmisano (Institute of Labor Economics (IZA), 2023)
We suggest a simple and flexible criterion to assess relative inter-generational mobility. It accommodates different types of outcomes, such as (continuous) earnings or (discrete and ordinal) education levels, and captures dynastic improvements of such outcomes at different points of the initial distribution. We provide dominance characterizations – for instance on the relative progress made by women vs. men – that are consistent with social preferences upon desirable patterns of mobility. We suggest an application on Indonesia. Using the IFLS data, we match parents observed in 1993 to their children in 2014, providing one of the rare intergenerational mobility analyses based on a long panel in the context of a developing country. Results indicate that mobility in terms of education and potential earnings was markedly at the advantage of women. The bulk of the population came out of illiteracy, possibly due to large-scale education reforms, but the relative educational mobility was regressive, which considerably reduced the progressivity of mobility in terms of potential earnings.
Keywords: J6; J62; O12; 330; intergenerational mobility; education; earnings; social welfare; gender